Effectiveness of Mindfulness Intervention on Cognitive Functions: A Meta-analysis of Mindfulness Studies - Nazaribadie, Marzieh (2021)
Background: The experience of cognitive deficits is common among patients with degenerative and psychiatric disorders. Objective: The present study aimed to evaluate the effect of the empirical literature of mindfulness intervention on cognitive functions. Methods: This study was conducted in June 2020 by using the scientific records were retrieved by a systematic search of several bibliographic databases on the Medline, Scopus, ISI Web of Sciences, Google scholar database from 2000 to 2020 for testing the effect of mindfulness intervention on cognitive functions. For data analysis CMA2 software were used. Heterogeneity assessed by Cochran’s Q statistics test. Publication Bias assessed by Orwin fail safe N, Begg’s method kendall’s Tau, Egger’s method intercept and funnel plot. Results: from 17 initial studies, 28 effect sizes were calculated. Among the 28 effect sizes, 6 indicators were negative and 22 indicators were positive. key results from the meta-analysis, Compared to healthy controls showed that people were receive mindfulness intervention significantly improved in working memory and attention function, with this enhance medium magnitude (Hedges’ g = 0.32, 0.35 respectively, see Figure 2). There was no significant improve by use mindfulness intervention on executive function. Conclusions: The results prove the initial evidence that mindfulness intervention can improve some neurocognitive processing such as attention function and working memory